2002
DOI: 10.1002/etc.5620210822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethinylestradiol on the reproduction and induction of vitellogenin and testis‐ova in medaka (Oryzias latipes)

Abstract: Mature medaka (Oryzias latipes) were exposed to ethinylestradiol (EE2) at measured concentrations of 32.6, 63.9, 116, 261, and 488 ng/L for 21 d under flow-through conditions. Effects on reproductive success of the fish as well as on gonadal condition and vitellogenin (VTG) induction were assessed. A significant decrease in fecundity was observed only at the highest EE2 concentration, whereas hepatic VTG concentration in males was increased at concentrations of 63.9 ng/L and greater. In addition, an intersex c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(22 citation statements)
references
References 41 publications
5
17
0
Order By: Relevance
“…Gray et al (1999) also reported that exposure of male medaka to octylphenol during early life induce swollen abdomens and, subsequently, complete mortality before maturation. Similar pathological symptoms were observed in adult male medaka exhibiting increased VTG levels as a result of exposure to estrogenic compounds (Kang et al, 2002b;Seki et al, 2002). These authors suggested that general peritoneal edema related to ascites caused the mortality in males, because the male medaka has no natural process to excrete VTG accumulated in excess, causing pathological effects.…”
Section: Discussionsupporting
confidence: 56%
“…Gray et al (1999) also reported that exposure of male medaka to octylphenol during early life induce swollen abdomens and, subsequently, complete mortality before maturation. Similar pathological symptoms were observed in adult male medaka exhibiting increased VTG levels as a result of exposure to estrogenic compounds (Kang et al, 2002b;Seki et al, 2002). These authors suggested that general peritoneal edema related to ascites caused the mortality in males, because the male medaka has no natural process to excrete VTG accumulated in excess, causing pathological effects.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, the exposure continued for an additional 1 mo in optimal reproductive temperatures (25-27°C) to prepare the fish for reproductive evaluation. In comparison with existing references, egg production (12-16 eggs/pair/d) in the control group of this study was well within the normal range of medaka fish reproduction (12-30 eggs/ pair/d) reported previously (Kang et al, 2002;Seki et al, 2002Seki et al, , 2005. The reduced egg production (0-9 eggs/pair/d) in E2-treated control and SAR-GW groups was similar to fish exposed to 27.9 ng/L E2 in a full-life-cycle exposure (0-5.4 eggs/pair/d) (Seki et al, 2005).…”
Section: Discussionsupporting
confidence: 83%
“…However, 20-30% mortality occurred in the E2-treated control and SAR-GW groups during the 1-mo static exposure. Although analytical confirmation of E2 exposure was not conducted, the occurrence of mortality, swollen abdomen, and lightened body color of the deaths indicated signs typical of E2 exposure in high concentrations or similar concentrations of chronic exposure (Kang et al, 2002;Seki, et al, 2002Seki, et al, , 2005.…”
Section: Mortalitymentioning
confidence: 96%
“…A decrease of testicular growth in male trout can be observed at the EEQ values in the range 10-100 ng L −1 (Harries et al 1997). The production of testis-ova in the testes of male medaka can be noticed at EEQ >100 ng L −1 level (Seki et al 2002). Hence, the EDCs in East Dongting Lake and Honghu Lake at specific sites may induce biological effects on the endocrine system of aquatic organisms, if the exposure to these levels is of sufficient duration.…”
Section: Estimation Of Endocrine-disrupting Compound Estrogenicitymentioning
confidence: 94%